Produksi Wacana Masyarakat Kota Semarang terhadap Lagu Genjer-genjer dan Partai Komunis Indonesia (PKI) - Alifiandra, Natasha; -, Bandiyah; Pramana, Gede Indra (Jurnal Nawala Politika, 2021)
The purpose of this study was to determine the production produced by the people of Semarang City in viewing the songs of Genjer-genjer and PKI.. This study uses the theory of discourse by Michel Foucault, this theory is important to reveal the existence and relationship between knowledge and power in society so as to give birth to a discourse that is believed by the community as a truth. The author uses a qualitative research method with a Foucaultdian Discourse Analysis approach. This shows that strong cultural reproduction has shaped the memory of the people of Semarang that the song Genjer-genjer was originally a musical art, now it has become a negative song because it has always been identified with the PKI. This shows that the incident still leaves a network of fear in the community, public discourse on this topic is still polarized in a negative way. Keywords: Genjer-genjer song, PKI, Discourse Production, New Order, Semarang society, Foucault.